Good Company - Arthur, Blank (Collins Publishers, 2020)
Arthur M. Blank believes that for good companies, purpose and profit can-and should-go hand in hand. And he should know. Together with cofounder Bernie Marcus, Blank built The Home Depot from an idea and a dream to a
Includes index
Keywords: Business